Does Intraspecific Variation in rDNA Copy Number Affect Analysis of Microbial Communities?. Issue 1 (January 2021) - Lavrinienko, Anton; Jernfors, Toni; Koskimäki, Janne J.; Pirttilä, Anna Maria; Watts, Phillip C.
Abstract : Amplicon sequencing of partial regions of the ribosomal RNA loci (rDNA) is widely used to profile microbial communities. However, the rDNA is dynamic and can exhibit substantial interspecific and intraspecific variation in copy number in prokaryotes and, especially, in microbial eukaryotes. As change in rDNA copy number is a common response to environmental change, rDNA copy number is not necessarily a property of a species. Variation in rDNA copy number, especially the capacity for large intraspecific changes driven by external cues, complicates analyses of rDNA amplicon sequence data. We highlight the need to (i) interpret amplicon sequence data in light of possible interspecific and intraspecific variation, and (ii) examine the potential plasticity in rDNA copy number as an important ecological factor to better understand how microbial communities are structured in heterogeneous environments. Highlights: Amplicon sequencing of part of the ribosomal RNA locus (hereafter, rDNA) is a widespread methodology that has uncovered vast diversity and macroecological patterns in microbial communities. While interspecific variation in rDNA copy number may complicate analyses of microbial communities using amplicon sequence data, the occurrence of intraspecific variation in rDNA copy number adds an extra dimension of complexity. As intraspecific variation in rDNA copy number is associated with environment variation, apparent demographic changes in a microbial community may be driven by a genomic response to the environment. Intraspecific variation in rDNA copy number may be a greater problem for studies of microbial eukaryotes than prokaryotes, and hence the challenge in interpreting amplicon sequence data.